Rapid riparian ecosystem decline in Rocky Mountain National Park - David J. Cooper; E. William Schweiger; Jeremy R. Shaw; Cherie J. Westbrook; Kristen Kaczynski; Hanem Abouelezz; Scott M. Esser; Koren Nydick; Isabel de Silva; Rodney A. Chimner (Conservation Biology, 2025)
Understanding the drivers of ecosystem collapse is critical for resource management, particularly for protected areas mandated to preserve biodiversity. In Rocky Mountain National Park, Colorado, tall willows ( Salix spp.) dominated riparian vegetation, and a beaver–willow state was the natural ecosystem type in the Colorado River headwaters. However, willows comprise a portion of elk diets and are a preferred food for recently introduced moose, and the vegetation structure has changed dramatically since the early 2000s. To assess ecosystem changes, we analyzed time‐series data on willow height from 1997 to 2021 inside and outside 3 exclosures built to exclude ungulates, area of tall willows in 1999 and 2019, area of open water from 1953 to 2019, vegetation composition in 1998 and 2021, groundwater depth from 1996 to 2021, surface water flow from 1953 to 2023, and climate from 1950 to 2023. Tall willow coverage and open water area declined by >90% from 1999 to 2019. Willow height outside the ungulate exclosures declined by more than 75% since the 1990s; yet, within exclosures that were formerly browsed, willow height increased by up to 500%. Tall willow communities have largely been replaced by grasslands. Browsing by elk and moose likely played a pivotal role in triggering a collapse of the beaver–willow state and the formation of an alternative moose–elk–grassland state that appears stable and may be difficult to reverse without direct human action. Restoration efforts will depend on a reduction in herbivory and reconnection of the river with its floodplain.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

The invasion threat of the emerging alien cactus Cylindropuntia pallida (Rosa), F.M. Knuth in South Africa and the potential for control using herbicides - Thabiso Michael Mokotjomela; Takalani Nelufule; Zimbini Scott; Loyd Rodney Vukeya; Travor Xivuri; King Matsokane; Nobuhle Mweli; Felicia Lerato Magqabi; Thulisile Jaca (Environmental Monitoring and Assessment, 2024)
The emerging alien cactus Cylindropuntia pallida (Rose) F.M. Knuth originates from northern Mexico and introduced into South Africa in 1940s as an ornamental plant. Multiple populations of C. pallida have been detected in various areas of South Africa. C. pallida has effective propagule dispersal and rapid recruitment making it a likely key future invader, and thus, is a target for eradication in South Africa. To eradicate C. pallida populations, a foliar spray (i.e. using a 2% concentration of herbicide with fluroxypyr and triclopyr) has been applied to plants in nine populations, with population sizes ranging between 535 and 2701 plants and populations covering areas of 100 –1000 ha. The aims of the study were to investigate the efficacy of the foliar spray method used to eradicate C. pallida ; to investigate the impacts of C. pallida invasions on native vegetation integrity; to apply species distribution models (SDMs) to identify suitable climates for C. pallida in South Africa; and to document the biomes vulnerable to the negative impact of C. pallida in South Africa. Results show that foliar spray killed many C. pallida plants (mean percentage of dead plants ± SE, 83.3 ± 6.4; n = 9; range, 70–96%), with adult plants taking about 2 months to die completely. The efficacy of the herbicide was not affected by plant size or the concentration of the herbicide used. The invaded site had significantly greater vegetation cover which persisted across winter compared to the uninvaded site, but the latter site’s vegetation cover significantly dropped in winter. Also, the invaded site had lower plant species diversity than the uninvaded site and was dominated by species in the Poaceae and Asteraceae plant families. Additionally, a normalised difference vegetation index (NDVI) analysis shows that the uninvaded site has higher vegetation cover and health than the invaded site wherein a notable decline in vegetation health was observed between 2019 and 2022. A large area (> 15 million hectares) was predicted to be suitable for invasion by C. pallida in provinces with arid and warm temperate climates - the fynbos and grassland biomes are the most vulnerable. Because of the observed negative impacts, high environmental compatibility, and high cost of clearing large infestations, we advocate for considering the biocontrol method for effectively managing C. pallida invasion in South Africa.

Efficacy of grape seed procyanidins for inhibiting denitrification varies by source, soil texture, and cropping history - Che-Jen Hsiao; Alexander Frie; Scott Mitchell; Rodney Venterea; Timothy Griffis (Applied Soil Ecology, 2024)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

High polygenic risk score for exceptional longevity is associated with a healthy metabolic profile - Mary Revelas; Anbupalam Thalamuthu; Anna Zettergren; Christopher Oldmeadow; Jenna Najar; Nazib M. Seidu; Nicola J. Armstrong; Carlos Riveros; John B. Kwok; Peter R. Schofield; Julian N. Trollor; Margda Waern; et al. (GeroScience, 2023)
Healthy metabolic measures in humans are associated with longevity. Dysregulation leads to metabolic syndrome (MetS) and negative health outcomes. Recent exceptional longevity (EL) genome wide association studies have facilitated estimation of an individual’s polygenic risk score (PRS) for EL. We tested the hypothesis that individuals with high ELPRS have a low prevalence of MetS. Participants were from five cohorts of middle-aged to older adults. The primary analyses were performed in the UK Biobank (UKBB) ( n = 407,800, 40–69 years). Replication analyses were undertaken using three Australian studies: Hunter Community Study ( n = 2122, 55–85 years), Older Australian Twins Study ( n = 539, 65–90 years) and Sydney Memory and Ageing Study ( n = 925, 70–90 years), as well as the Swedish Gothenburg H70 Birth Cohort Studies ( n = 2273, 70–93 years). MetS was defined using established criteria. Regressions and meta-analyses were performed with the ELPRS and MetS and its components. Generally, MetS prevalence (22–30%) was higher in the older cohorts. In the UKBB, high EL polygenic risk was associated with lower MetS prevalence (OR = 0.94, p = 1.84 × 10 –42 ) and its components ( p < 2.30 × 10 – 8 ). Meta-analyses of the replication cohorts showed nominal associations with MetS ( p = 0.028) and 3 MetS components ( p < 0.05). This work suggests individuals with a high polygenic risk for EL have a healthy metabolic profile promoting longevity.

New Zealand southern right whale (Eubalaena australis; Tohorā nō Aotearoa) behavioural phenology, demographic composition, and habitat use in Port Ross, Auckland Islands over three decades: 1998–2021 - Emma L. Carroll; Leena Riekkola; Virginia Andrews-Goff; C. Scott Baker; Rochelle Constantine; Ros Cole; Kim Goetz; Robert Harcourt; David Lundquist; Catherine Meyer; Mike Ogle; Richard O’Rorke; et al. (Polar Biology, 2022)
Changes in habitat availability and prey abundance are predicted to adversely influence survival and reproduction of wildlife in the Southern Ocean. Some populations of southern right whale (SRW; Eubalaena australis ) are showing dramatic changes in habitat use. Surveys were undertaken in the austral winters of 2020 and 2021 at the key nursery and socialising ground for New Zealand SRWs: Port Ross, Auckland Islands, with 548 encounters and 599 skin biopsy samples collected. Data from these two surveys spanned peak periods of use and were used to test the hypothesis there have been shifts in the phenology, demographic composition and behaviour of SRWs using the Auckland Islands over the past three decades. The behavioural phenology and demographic composition of SRW resembles that observed in the 1990s. In contrast, the proportion of groups containing cow-calf pairs increased from 20% in the 1998 survey to 50% in 2020/21. These changes are consistent with a growing population undergoing strong recruitment, not limited by food resources. Continued use of Port Ross by all SRW demographic classes confirms this as key habitat for SRW in New Zealand waters, and we support increased enforcement of existing management measures to reduce whale-vessel interactions in this remote subantarctic archipelago.

A new species, new host records and life cycle data for lepocreadiids (Digenea) of pomacentrid fishes from the Great Barrier Reef, Australia - Berilin Duong; Scott C. Cutmore; Thomas H. Cribb; Kylie A. Pitt; Nicholas Q.-X. Wee; Rodney A. Bray (Systematic Parasitology, 2022)
A new species of lepocreadiid, Opechonoides opisthoporus n. sp. , is described infecting 12 pomacentrid fish species from the Great Barrier Reef, Australia, with Abudefduf whitleyi Allen & Robertson as the type-host. This taxon differs from the only other known member of the genus, Opechonoides gure Yamaguti, 1940, in the sucker width ratio, cirrus-sac length, position of the testes, position of the pore of Laurer’s canal, and relative post-testicular distance. The new species exhibits stenoxenic host-specificity, infecting pomacentrids from seven genera: Abudefduf Forsskål, Amphiprion Bloch & Schneider, Neoglyphidodon Allen, Neopomacentrus Allen, Plectroglyphidodon Fowler & Ball, Pomacentrus Lacépède and Stegastes Jenyns. Phylogenetic analyses of 28S rDNA sequence data demonstrate that O. opisthoporus n. sp. forms a strongly supported clade with Prodistomum orientale (Layman, 1930) Bray & Gibson, 1990. The life cycle of this new species is partly elucidated on the basis of ITS2 rDNA sequence data; intermediate hosts are shown to be three species of Ctenophora. New host records and molecular data are reported for Lepocreadium oyabitcha Machida, 1984 and Lepotrema amblyglyphidodonis Bray, Cutmore & Cribb, 2018, and new molecular data are provided for Lepotrema acanthochromidis Bray, Cutmore & Cribb, 2018 and Lepotrema adlardi (Bray, Cribb & Barker, 1993) Bray & Cribb, 1996. Novel cox 1 mtDNA sequence data showed intraspecific geographical structuring between Heron Island and Lizard Island for L. acanthochromidis but not for L. adlardi or O. opisthoporus n. sp.

Variable vulnerability to climate change in New Zealand lizards - Scott Jarvie; Travis Ingram; David G. Chapple; Rodney A. Hitchmough; Stuart V. Nielsen; Joanne M. Monks (Journal of Biogeography, 2022)
Aim The primary drivers of species and population extirpations have been habitat loss, overexploitation and invasive species, but human‐mediated climate change is expected to be a major driver in future. To minimise biodiversity loss, conservation managers should identify species vulnerable to climate change and prioritise their protection. Here, we estimate climatic suitability for two species‐rich taxonomic groups, then use phylogenetic analyses to assess vulnerability to climate change. Location Aotearoa New Zealand (NZ). Taxa NZ lizards: diplodactylid geckos and eugongylinae skinks. Methods We built correlative species distribution models (SDMs) for NZ geckos and skinks to estimate climatic suitability under current climate and 2070 future climate scenarios. We then used Bayesian phylogenetic mixed models (BPMMs) to assess vulnerability for both groups with predictor variables for life‐history traits (body size and activity phase) and current distribution (elevation and latitude). We explored two scenarios: an unlimited dispersal scenario, where projections track climate, and a no‐dispersal scenario, where projections are restricted to areas currently identified as suitable. Results SDMs projected vulnerability to climate change for most modelled lizards. For species' ranges projected to decline in climatically suitable areas, average decreases were between 42% and 46% for geckos and 33% and 52% for skinks, although area did increase or remain stable for a minority of species. For the no‐dispersal scenario, the average decrease for geckos was 37%–52% and for skinks was 33%–52%. Our BPMMs showed phylogenetic signal in climate change vulnerability for both groups, with elevation increasing vulnerability for geckos, and body size reducing vulnerability for skinks. Main conclusions New Zealand lizards showed variable vulnerability to climate change, with most species' ranges predicted to decrease. For species whose suitable climatic space is projected to disappear from within their current range, managed relocation could be considered to establish populations in regions that will be suitable under future climates.

Eight species of Lintonium Stunkard & Nigrelli, 1930 (Digenea: Fellodistomidae) in Australian tetraodontiform fishes - Thomas H. Cribb; Storm B. Martin; Pablo E. Diaz; Rodney A. Bray; Scott C. Cutmore (Systematic Parasitology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Lung Cancer Occurrence—Correlation with Serum Chromium Levels and Genotypes - Piotr Baszuk; Beata Janasik; Sandra Pietrzak; Wojciech Marciniak; Edyta Reszka; Katarzyna Białkowska; Ewa Jabłońska; Magdalena Muszyńska; Monika Lesicka; Róża Derkacz; Tomasz Grodzki; Janusz Wójcik; et al. (Biological Trace Element Research, 2021)
Lung cancer is the leading cause of cancer-related death worldwide. Exposure to environmental and occupational carcinogens is an important cause of lung cancer. One of these substances is chromium, which is found ubiquitously across the planet. The International Agency for Research on Cancer has classified chromium(VI) as a human carcinogen. The aim of this study was to assess whether serum chromium levels, as well as DNA variants in selected genes involved in carcinogenesis, xenobiotic-metabolism, and oxidative stress could be helpful in the detection of lung cancer. We conducted a study using 218 lung cancer patients and 218 matched healthy controls. We measured serum chromium levels and genotyped ten genetic variants in ERCC2 , XRCC1 , MT1B , GSTP1 , ABCB1 , NQ01 , CRTC3 , GPX1 , SOD2 and CAT . The odds ratios of being diagnosed with lung cancer were calculated using conditional logistic regression with respect to serum chromium level and genotypes. The odds ratio for the occurrence of lung cancer increased with increasing serum chromium levels. The difference between the quartiles with the lowest vs. highest chromium level was more than fourfold in the entire group (OR 4.52, CI 2.17–9.42, p < 0.01). This correlation was significantly increased by more than twice when specific genotypes were taken into consideration ( ERCC –rs12181 TT, OR 12.34, CI 1.17–130.01, p = 0.04; CRTC3 –rs12915189 non GG, OR 9.73, CI 1.58–60.10, p = 0.01; GSTP1 –rs1695 non AA, OR 9.47, CI 2.06–43.49, p = < 0.01; CAT –rs1001179 non CC, OR 9.18, CI 1.64–51.24, p = 0.01). Total serum chromium levels > 0.1 μg/L were correlated with 73% (52/71) of lung cancers diagnosed with stage I disease. Our findings support the role of chromium and the influence of key proteins on lung cancer burden in the general population.

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

The future of barriers and trapping methods in the sea lamprey (Petromyzon marinus) control program in the Laurentian Great Lakes - Scott Miehls; Paul Sullivan; Michael Twohey; Jessica Barber; Rodney McDonald (Reviews in Fish Biology and Fisheries, 2020)
A major duty of the Great Lakes Fishery Commission (GLFC), created in 1955, was the development a program of eradication or management of sea lamprey populations in the Great Lakes for the protection of the Great Lakes fishery. Beginning in the 1980s the GLFC shifted sea lamprey control to an integrated pest management model seeking to deploy control measures which target multiple life stages. Currently control efforts focus on limiting the area of infestation using barriers to migratory adults and eradication of larvae from streams using selective pesticides. Feedback on program effectiveness is obtained by trapping migratory adult lamprey at a series of index sites around the basin. The GLFC continues to support multiple research initiatives to develop additional control, improve current control measures, and further advance the sea lamprey control program. During the past six decades sea lamprey control in the Great Lakes has evolved as the research program has identified technological advances. Here we summarize the current state and recent advancements for two of the sea lamprey control program’s core elements, barriers and traps, highlight challenges to be addressed to continue the advancement of these program elements, and provide a series of research questions to spur interest within the research community. Further, because considerable information about these program elements is scattered among grey literature and technical reports, we summarize the history of barriers and traps in sea lamprey control in the included appendices to provide relevant program background to anyone interested in pursuing these research topics.

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Lepotrema Ozaki, 1932 (Lepocreadiidae: Digenea) from Indo-Pacific fishes, with the description of eight new species, characterised by morphometric and molecular features - Rodney A. Bray; Scott C. Cutmore; Thomas H. Cribb (Systematic Parasitology, 2018)

Two new species of Bacciger Nicoll, 1914 (Trematoda: Faustulidae) in species of Herklotsichthys Whitley (Clupeidae) from Queensland waters - Scott C. Cutmore; Rodney A. Bray; Thomas H. Cribb (Systematic Parasitology, 2018)

Lepocreadiidae Odhner, 1905 and Aephnidiogenidae Yamaguti, 1934 (Digenea: Lepocreadioidea) of fishes from Moreton Bay, Queensland, Australia, with the erection of a new family and genus - Rodney A. Bray; Thomas H. Cribb; Scott C. Cutmore (Systematic Parasitology, 2018)

Three members of Opisthomonorcheides Parukhin, 1966 (Digenea: Monorchiidae) from carangid fishes (Perciformes) from Indonesia, with a review of the genus - Rodney A. Bray; Harry W. Palm; Scott C. Cutmore; Thomas H. Cribb (Systematic Parasitology, 2017)

Anisotropic mechanical properties of zircon and the effect of radiation damage - Tobias Beirau; William D. Nix; Ulrich Bismayer; Lynn A. Boatner; Scott G. Isaacson; Rodney C. Ewing (Physics and Chemistry of Minerals, 2016)

Trematodes of fishes of the Indo-west Pacific: told and untold richness - Thomas H. Cribb; Rodney A. Bray; Pablo E. Diaz; Daniel C. Huston; Olena Kudlai; Storm B. Martin; Russell Q.-Y. Yong; Scott C. Cutmore (Systematic Parasitology, 2016)

Biogeochemical Research Priorities for Sustainable Biofuel and Bioenergy Feedstock Production in the Americas - Hero T. Gollany; Brian D. Titus; D. Andrew Scott; Heidi Asbjornsen; Sigrid C. Resh; Rodney A. Chimner; Donald J. Kaczmarek; Luiz F. C. Leite; Ana C. C. Ferreira; Kenton A. Rod; Jorge Hilbert; Marcelo V. Galdos; et al. (Environmental Management, 2015)

A review of the genus Antorchis Linton, 1911 (Trematoda: Faustulidae) from Indo-Pacific fishes with the description of a new species - Thomas H. Cribb; Rodney A. Bray; Kathryn A. Hall; Scott C. Cutmore (Systematic Parasitology, 2015)

Polymorphisms in nucleotide excision repair genes and susceptibility to colorectal cancer in the Polish population - Katarzyna Paszkowska-Szczur; Rodney J. Scott; Bohdan Górski; Cezary Cybulski; Grzegorz Kurzawski; Dagmara Dymerska; Satish Gupta; Thierry van de Wetering; Bartłomiej Masojć; Aniruddh Kashyap; Paulina Gapska; Tomasz Gromowski; et al. (Molecular Biology Reports, 2015)

Rare germline copy number deletions of likely functional importance are implicated in endometrial cancer predisposition - Gemma L. Moir-Meyer; John F. Pearson; Felicity Lose; Rodney J. Scott; Mark McEvoy; John Attia; Elizabeth G. Holliday; Paul D. Pharoah; Alison M. Dunning; Deborah J. Thompson; Douglas F. Easton; Amanda B. Spurdle; et al. (Human Genetics, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

A new species of Plectognathotrema Layman, 1930 (Trematoda: Zoogonidae) from an Australian monacanthid, with a molecular assessment of the phylogenetic position of the genus - Scott C. Cutmore; Terrence L. Miller; Rodney A. Bray; Thomas H. Cribb (Systematic Parasitology, 2014)

Erratum to: Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Erratum to: Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Pseudobacciger cheneyae n. sp. (Digenea: Gymnophalloidea) from Weber’s chromis (Chromis weberi Fowler & Bean) (Perciformes: Pomacentridae) at Lizard Island, Great Barrier Reef, Australia - Derek Sun; Rodney A. Bray; Russell Q.-Y. Yong; Scott C. Cutmore; Thomas H. Cribb (Systematic Parasitology, 2014)

The sexual adult of Cercaria praecox Walker, 1971 (Digenea: Fellodistomidae), with the proposal of Oceroma n. g. - Thomas H. Cribb; Terrence L. Miller; Rodney A. Bray; Scott C. Cutmore (Systematic Parasitology, 2014)

Childhood and parental diagnostic radiological procedures and risk of childhood brain tumors - Elizabeth Milne; Kathryn R. Greenop; Lin Fritschi; John Attia; Helen D. Bailey; Rodney J. Scott; Lesley J. Ashton; Elizabeth Smibert; Bruce K. Armstrong (Cancer Causes & Control, 2014)

Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Recovery from topkill of shortleaf pine × loblolly pine hybrids compared to their parent populations - Rodney E. Will; Curtis J. Lilly; John Stewart; Scott Huff; C. G. Tauer (Trees, 2013)

Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2013)

Genetic modifiers of cancer risk in Lynch syndrome: a review - Bente A. Talseth-Palmer; Juul T. Wijnen; Desma M. Grice; Rodney J. Scott (Familial Cancer, 2013)

Parental alcohol consumption and risk of childhood acute lymphoblastic leukemia and brain tumors - Elizabeth Milne; Kathryn R. Greenop; Rodney J. Scott; Nicholas H. de Klerk; Carol Bower; Lesley J. Ashton; John A. Heath; Bruce K. Armstrong (Cancer Causes & Control, 2013)

Evaluating the effectiveness of road mitigation measures - Edgar A. van der Grift; Rodney van der Ree; Lenore Fahrig; Scott Findlay; Jeff Houlahan; Jochen A. G. Jaeger; Nina Klar; L. Francisco Madriñan; Leif Olson (Biodiversity and Conservation, 2013)

Peracreadium akenovae sp. nov. (Trematoda: Opecoelidae) parasitising the highfin moray eel Gymnothorax pseudothyrsoideus (Anguilliformes: Muraenidae) from moreton bay, Australia - Thomas Cribb; Rodney Bray; Scott Cutmore (Acta Parasitologica, 2013)
A new opecoelid trematode, Peracreadium akenovae sp. nov., is described from the highfin moray eel Gymnothorax pseudothyrsoideus (Bleeker) (Anguilliformes; Muraenidae), collected from Moreton Bay off southeast Queensland, Australia. The new species is distinctive in its body shape, transversely elongate irregular testes, vitelline follicles interrupted at the level of the ventral sucker, and diverticulate excretory vesicle. The Muraenidae is a new host family for Peracreadium Nicoll, 1909. Peracreadium is the seventh opecoelid genus reported from temperate eastern Australian marine fishes and this is its first report from Australian waters.

Integrating Climate and Ocean Change Vulnerability into Conservation Planning - Elizabeth McLeod; Alison Green; Edward Game; Kenneth Anthony; Joshua Cinner; Scott F. Heron; Joanie Kleypas; Catherine E. Lovelock; John M. Pandolfi; Robert L. Pressey; Rodney Salm; Steve Schill; et al. (Coastal Management, 2012)

Maternal consumption of coffee and tea during pregnancy and risk of childhood ALL: results from an Australian case–control study - Elizabeth Milne; Jill A. Royle; Lisa C. Bennett; Nicholas H. de Klerk; Helen D. Bailey; Carol Bower; Margaret Miller; John Attia; Rodney J. Scott; Maria Kirby; Bruce K. Armstrong (Cancer Causes & Control, 2011)

Positive Allosteric Interaction of Structurally Diverse T-Type Calcium Channel Antagonists - Victor N. Uebele; Cindy E. Nuss; Steven V. Fox; Susan L. Garson; Razvan Cristescu; Scott M. Doran; Richard L. Kraus; Vincent P. Santarelli; Yuxing Li; James C. Barrow; Zhi-Qiang Yang; Kelly-Ann S. Schlegel; et al. (Cell Biochemistry and Biophysics, 2009)

Auranofin disrupts selenium metabolism in Clostridium difficile by forming a stable Au–Se adduct - Sarah Jackson-Rosario; Darin Cowart; Andrew Myers; Rebecca Tarrien; Rodney L. Levine; Robert A. Scott; William Thomas Self (JBIC Journal of Biological Inorganic Chemistry, 2009)

Farmlink: promoting conservation buffers farmer-to-farmer - David P. Shelton; Rodney A. Wilke; Thomas G. Franti; Scott J. Josiah (Agroforestry Systems, 2009)

Relationship of intertidal surface sediment chlorophyll concentration to hyperspectral reflectance and chlorophyll fluorescence - Jacco C. Kromkamp; Edward P. Morris; Rodney M. Forster; Claire Honeywill; Scott Hagerthey; David M. Paterson (Estuaries and Coasts, 2006)

Progress in NTHMP Hazard Assessment - Frank I. Gonzlez; Vasily V. Titov; Harold O. Mofjeld; Angie J. Venturato; R. Scott Simmons; Roger Hansen; Rodney Combellick; Richard K. Eisner; Don F. Hoirup; Brian S. Yanagi; Sterling Yong; Mark Darienzo; et al. (Natural Hazards, 2005)

ELA-ICP-MS U?Pb zircon geochronology of regional volcanism hosting the Bajo de la Alumbrera Cu?Au deposit: implications for porphyry-related mineralization - Charlotte M. Allen; Scott E. Bryan; Ian H. Campbell; Rodney J. Holcombe; Anthony C. Harris; J. Michael Palin (Mineralium Deposita, 2004)

Profuse familial adenomatous polyposis with an Adenomatous Polyposis Coli exon 3 mutation - Steven Nasioulas; Ian T. Jones; D. James B. St. John; Rodney J. Scott; Susan M. Forrest; R. J. McKinlay Gardner (Familial Cancer, 2001)

Microsatellite markers for the deer mouse Peromyscus maniculatus - Scott E. Chirhart; Rodney L. Honeycutt; Ira F. Greenbaum (Molecular Ecology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)